Synthesis of protectin D1 analogs: novel pro-resolution and radiotracer agents. Issue 36 (11th September 2018) - Tungen, J. E.; Aursnes, M.; Ramon, S.; Colas, R. A.; Serhan, C. N.; Olberg, D. E.; Nuruddin, S.; Willoch, F.; Hansen, T. V.
Abstract : The first synthetic analog of protectin D1 with potent pro-resolving and anti-inflammatory properties is reported. Abstract : Protectin D1 is a specialized pro-resolving mediator with potent pro-resolving and anti-inflammatory effects in vivo in several human disease models. Herein the preparation of the first synthetic analog of protectin D1, named 22-F-PD1, is presented together with data from in vivo investigations. This analog showed potent pro-resolving and anti-inflammatory properties. These results inspired the preparation of the radiotracer 22-[ 18 F]F-PD1-ME that was used in a positron emission tomography proof of concept study. Altogether, the findings presented contribute to new knowledge on the biomolecular properties of protectin D1 analogs. In addition, an improved formal synthesis of the metabolite 22-OH-PD1 is reported.